STUDIES ON NOVEL ENERGY AND NUTRIENTS SOURCE IN AFRICAN STAR APPLE (Chrysophyllum albidum) FOR FEEDING POULTRY. - Annongu, Azor Amos; Adebisi, Adeyina Oluwatoba; Eunice, Sola-ojo Foluke; Solomon, Ajide, Olusoji; Joseph, Kolade; Hugues, Edoh Jphannes (Journal of Agricultural Sciences (Belgrade), 2017)
Abstract Investigations on graded levels of virgin (untreated) Star Apple Seed Kernel Meal, SASKM initially analysed for nutrients and phytochemical composition, were conducted. SASKM was included in diets at different levels to replace maize as the major source of energy in monogastric poultry diet. Data on proximate composition including minerals, vitamins, amino acids and quantification of some of the seed anti-nutrients showed that the seed is high in nutrients especially carbohydrate as source of energy but contains high levels of anti-nutritional or toxic factors. Performance traits of broilers fed SASKM gave poor results (p